Parallel Implementation of Random Walk Simulations with Different Movement Algorithms - Mirchev, Miroslav; Zdraveski, Vladimir; Basnarkov, Lasko; Nasteski, Andrej; Gushev, Marjan (IEEE, 2021)
This article contains a detailed explanation of the research, methodology and results of different searching strategies when traversing through an unknown area. We have been challenged by the ways to simulate and evaluate the effectiveness of various approaches in order to speed up the simulation using parallel computing. The goal is to compare the results from each combination of algorithms. The two categories of algorithms considered are direction based and step size based algorithms. In summary, the combination of exponential step size with backtracking and forward check direction algorithm produced the best results. We also concluded that using a parallel implementation resulted with a substantial speed up when compared to a sequential approach.
Keywords: random walk, search, parallel simulation